Costa Rican Education: Relationship between Mathematics Programs and Curricular Policy: Educación costarricense: relación entre los programas de Matemáticas y la política curricular - Zumbado-Castro, Marianela (2021)
The objective of the article is to show the relationship between the methodology proposed in the Mathematics programs and the dimensions of the curricular policy that are in force in Costa Rica. To achieve this objective, three sections are proposed. The first consists of an approach to the methodological strategy proposed in the mathematics programs approved by the Higher Council for Education (CSE) in 2012, including a practical example of the first stage called “Learning knowledge”. Secondly, a description of the dimensions of the curricular policy approved by the CSE in 2016 is presented and, finally, the third section shows how the Mathematics programs are related to these dimensions. As part of the final considerations, it is suggested that the teacher understand how the current methodological proposal for teaching and learning Mathematics is related to the dimensions of curricular policy, to enhance, through the moments of class, achieving the expectations of the educational system.